Responsiveness of the electrically stimulated cochlear nerve in patients with a missense variant in ACTG1: preliminary results - Yuan, Yi; Yan, Denise; Skidmore, Jeffrey; Chapagain, Prem; Liu, Xuezhong; He, Shuman (Frontiers in Audiology and Otology, 2023)
This preliminary study identified a missense variant in ACTG1 (NM_001614.5) in a family with autosomal dominant non-syndromic hearing loss (ADNSHL). The responsiveness of the electrically-stimulated cochlear nerve (CN) in two implanted participants with this missense change was also evaluated and reported. Genetic testing was done using a custom capture panel (MiamiOtoGenes) and whole exome sequencing. The responsiveness of the electrically-stimulated CN was evaluated in two members of this family (G001 and G004) using the electrically evoked compound action potential (eCAP). eCAP results from these two participants were compared with those measured three implanted patient populations: children with cochlear nerve deficiency, children with idiopathic hearing loss and normal-sized cochlear nerves, and postligually deafened adults. Sequencing of ACTG1 identified a missense c.737A>T (p. Gln246Leu) variant in ACTG1 (NM_001614.5) which is most likely the genetic cause of ADNSHL in this family. eCAP results measured in these two participants showed substantial variations. The results indicated the missense c.737A>T (p. Gln246Leu) variant in ACTG1 (NM_001614.5) co-segregated with hearing loss in this family. The responsiveness of the electrically-stimulated CN can vary among patients with the same genetic variants, which suggests the importance of evaluating the functional status of the CN for individual CI patients.